Construction of a spatial distribution model of wind energy characteristics - Ausheva, Nataliia; Shapovalova, Svitlana; Petrenko, Kateryna; Kardashov, Oleksandr; Sofiienko, Anton (Національний технічний університет "Харківський політехнічний інститут", 2024)
The aim of this article is to develop a model for the spatial distribution of wind energy characteristics across the territory of Ukraine. The subject of the study includes datasets of wind speed values, as well as methods of data correlation, validation, and interpolation. Research results. Based on NASA reanalysis datasets and measurement results from 70 meteorological stations in Ukraine, a dataset of paired wind speed data corresponding to the same location but obtained through different methods was created. Through a comparative analysis of regression task results, evaluated using machine learning models trained on the dataset, the Random Forest model was selected as the most accurate (based on RMSE, R², and Pearson correlation coefficient) for predicting wind speedc deviations in NASA reanalysis data to bring them closer to actual values. The Pearson correlation coefficient improved by 0.07 in the worst case and by 0.66 in the best case.

Метою статті є створення моделі просторового розподілу характеристик вітрової енергії на території України. Предмет дослідження-набори даних значень швидкості вітру, методи кореляції, валідації та інтерполяції даних. Результати дослідження. На основі наборів даних реаналізу NASA та результатів вимірювань на 70 метеорологічних станціях України створено датасет пар відповідних даних швидкості вітру, які відносяться до однієї локації, але отримані різними способами. На основі порівняльного аналізу результатів розв’язання задачі регресії навченими на отриманому датасеті моделями машинного навчання обрано оптимальну за точністю (метрики RMSE, R2, коефіцієнта кореляції Пірсона) модель Random Forestдля прогнозування зсуву значення швидкості вітру в даних реаналізу NASA.
Побудова моделі просторового розподілу характеристик вітрової енергії
Keywords: machine learning; global atmospheric models; MERRA-2; meteorological data; reanalysis data; wind speed interpolation; universal kriging; машинне навчання; глобальні атмосферні моделі; метеорологічні дані; дані повторного аналізу; інтерполяція швидкості вітру; універсальний кригінг